Study of intrinsic point defects in Tantalum after plastic deformation at liquid helium temperatures - Peretti Hollemoert, Hernán A.; Mondino, Manuel Ángel; Seeger, Alfred (Elsevier Sequoia S. A., 1980)
Fil: Peretti Hollemoert, Hernán A. Comisión Nacional de Energía Atómica; Argentina